A Tiered Arabic Language Boarding Program in an Indonesian Pesantren: Curriculum Design, Vocabulary Mastery, and Learning Outcomes - Zulfan Syahansyah; Muhammad Zaironi (Al-Wazan: Journal of Arabic Education, 2026)
Many Islamic boarding schools (pesantren) in Indonesia face challenges in developing effective Arabic language programs that not only improve communicative skills but also enable students to comprehend classical Islamic texts. This study examines the structure and educational outcomes of a tiered Arabic language boarding program at Pondok Pesantren Al-Khoirot Malang. The research aims to analyze the curriculum design, vocabulary-based learning approach, and the competencies developed through the program. A qualitative method with an ethnographic approach was employed to explore learning practices, institutional culture, and the immersive language environment within the Arabic dormitory. Data were collected through participant observation, interviews, and documentation of the six-level curriculum system. The findings reveal that the program adopts a progressive six-level structure emphasizing systematic vocabulary acquisition and daily language practice. At the initial level, students focus on memorizing and using Arabic vocabulary in everyday communication. In subsequent levels, vocabulary learning is integrated with the translation of Ta’lim al-‘Arabiyyah and classical Arabic texts. The study identifies three major outcomes: students demonstrate strong competence in understanding unvowelled classical Arabic texts, many graduates successfully enroll in Indonesian universities with Arabic-related programs, and a considerable number continue their studies at Al-Azhar University. This study contributes to Arabic language education by providing an effective model of tiered, vocabulary-based instruction that supports both linguistic proficiency and academic advancement in Islamic educational contexts